Memorandum of Understanding between the Harvard School of Public Health and James P. Grant School of Public Health at BRAC University (2005) - Harvard School of Public Health; James P. Grant School of Public Health, BRAC University (Harvard School of Public Health and James P. Grant School of Public Health, BRAC University, 2013)
Memorandum of Understanding President and Fellows of Harvard College, on behalf of the Harvard School of Public Health and James P. Grant School of Public Health at BRAC University.